2019
DOI: 10.15605/jafes.034.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism presenting as ST Elevation Myocardial Infarction - A Case Report

Abstract: A 31-year-old male, apparently well, presented with typical chest pain. His ECG showed ST-elevation from V1-V4 and echocardiogram revealed anteroseptal wall hypokinesia with ejection fraction of 45%. Normal coronary arteries were seen on coronary angiogram. A thyroid function test showed elevated free T4 levels with suppressed thyroid stimulating hormone (TSH). Treatment with thionamides and beta-blockers improved symptoms. Upon review 4 months later he was well. Repeat echocardiogram showed good ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Hyperthyroidism is proved as a higher risk to develop myocardial infraction (MI) causing thyrocardiac disease, which is similar to the other case studies. [21,22] In this research study, two factors are investigated including gender in female and age group of 19-39 for higher risk of suffering from thyrocardiac disease to develop MI. In terms of gender, female is more likely to suffer from hyperthyroidism than male, having higher chance to develop MI.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthyroidism is proved as a higher risk to develop myocardial infraction (MI) causing thyrocardiac disease, which is similar to the other case studies. [21,22] In this research study, two factors are investigated including gender in female and age group of 19-39 for higher risk of suffering from thyrocardiac disease to develop MI. In terms of gender, female is more likely to suffer from hyperthyroidism than male, having higher chance to develop MI.…”
Section: Discussionmentioning
confidence: 99%
“…In a community dwelling elderly population, low fT3 was linked to low muscle mass and poor physical ability (35). In MINOCA patients, two recent case studies have shown that thyroid diseases such as thyrotoxicosis may be a potential cause for MINOCA, suggesting that thyroid hormones may play an important role in the pathogenesis of MINOCA and may have an impact on the prognosis of such patients group (36,37). To the best of our knowledge, this is the first study to demonstrate a relationship between lower fT3 levels and increased risk of MACE and cardiovascular deaths in the MINOCA population.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of thyrotoxicosis are linked with Graves' disease and toxic nodular goiter [ 67 ]. Hyperthyroidism is widely documented to be linked to cardiovascular disease [ 68 ]. Fatal disorders such as acute myocardial infraction presentation might be present in patients suffering from thyrotoxicosis, as seen in one case report, in which the patient presented with elevated ST segments in leads II, III, and aVF, as well as pressure-like chest discomfort and an increased troponin level.…”
Section: Reviewmentioning
confidence: 99%